2015
DOI: 10.1055/s-0035-1549378
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Urinary Tract Injuries: Etiology, Diagnosis, and Management

Abstract: Iatrogenic injury to the urinary tract, including the kidneys, ureters, bladder, and urethra, is a potential complication of surgical procedures performed in or around the retroperitoneal abdominal space or pelvis. While both diagnostic and interventional radiologists often play a central and decisive role in the identification and initial management of a variety of iatrogenic injuries, discussions of these injuries are often directed toward specialists such as urologists, obstetricians, gynecologists, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Studies have shown that use of coil embolization has little effect on renal function. 18 Gelatin sponge particles are large and embolized arteries can be recanalized, and thus this method is relatively safe. Therefore, gelatin sponge particles can be used as a supplementary embolization after coil embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that use of coil embolization has little effect on renal function. 18 Gelatin sponge particles are large and embolized arteries can be recanalized, and thus this method is relatively safe. Therefore, gelatin sponge particles can be used as a supplementary embolization after coil embolism.…”
Section: Discussionmentioning
confidence: 99%
“…A locally advanced tumour stage, rectal carcinoma recurrence, and previous RT also increase the anatomical distortions [11, 12]. Ninety per cent of all iatrogenic injuries to the ureter develop in the distal part of the ureter [13]. A curative resection is possible via the development of new surgical techniques and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although intra-operative identification and repair of ureteral injuries is associated with better outcomes, 50%–70% of these lesions are missed in acute settings [ 7 ]. Patients with unrecognized injuries can show abdominal pain, fever, anuria, peritonitis, and even vaginal urinary leaking [ 8 ]. In these patients, radiologists play a pivotal role in both the diagnosis of the injury and tailoring of treatment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%